The truths and lies of nationalism ; as narrated by Charvak - Chatterjee, Partha, 1947- (Albany : SUNY Press, 2022)
Rejects Hindu nationalism and pluralist secularism in favor of a revitalized politics of Indian federalism.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Cārvāka.; Cārvāka; Nationalism -- India -- History; Democracy -- India; Hindutva; India -- Politics and government; Inde -- Politique et gouvernement; Intégrisme hindou; HISTORY / Asia / South / General; Hindutva; Democracy; Nationalism; Politics and government; India; History